1996
DOI: 10.1210/jcem.81.5.8626853
|View full text |Cite
|
Sign up to set email alerts
|

High-dose growth hormone treatment of short children born small for gestational age.

Abstract: The effect of GH administration was evaluated over 2 yr in 50 short, prepubertal, non-GH deficient children born small for gestational age, who had been randomly allocated to a group receiving no treatment or daily sc GH treatment at a dose of 0.2 or 0.3 IU/kg. At the start of the study, mean age was 5.2 yr, bone age was 4.0 yr, height SDS was -3.5, height velocity SDS was -0.8, weight SDS was -2.7, and body mass index SDS was -1.9. Catch-up growth was observed in none of the untreated and all of the treated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 24 publications
6
25
1
2
Order By: Relevance
“…It has been suggested that short SGA children may have a degree of IGF-I resistance as higher basal and GH-induced IGF-I levels are required to achieve a growth velocity similar to that of other children (40). Relative IGF-I resistance at the pituitary could contribute to the elevated GH secretion seen in our short SGA children, and would also be compatible with the observation that supra-physiologic GH doses are required to significantly improve final height prognosis in short SGA children (41)(42)(43). Thus, short SGA children may appear to have a shift in the set point of their GH/IGF-I axis.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…It has been suggested that short SGA children may have a degree of IGF-I resistance as higher basal and GH-induced IGF-I levels are required to achieve a growth velocity similar to that of other children (40). Relative IGF-I resistance at the pituitary could contribute to the elevated GH secretion seen in our short SGA children, and would also be compatible with the observation that supra-physiologic GH doses are required to significantly improve final height prognosis in short SGA children (41)(42)(43). Thus, short SGA children may appear to have a shift in the set point of their GH/IGF-I axis.…”
supporting
confidence: 71%
“…Thus, children with GH deficiency or GH receptor deficiency tend to be obese (45,46). However, as in our study, short SGA children are often thin (17,19,41), suggesting that they remain sensitive to the metabolic effects of GH. The elevated pattern of GH secretion seen in our short SGA children is similar to that observed during fasting or malnutrition (47) and could lead to increased lipolysis and the development of insulin resistance.…”
supporting
confidence: 52%
“…Current criteria and modalities for GH intervention in short children born small for gestational age (SGA) have been based on a series of clinical studies (1)(2)(3). The initial GH-induced catch up growth in these children has been shown to be influenced by age at start of therapy, weight, and height SDS and mid-parental height, as well as GH dose (4).…”
Section: Introductionmentioning
confidence: 99%
“…Initial data were disappointing, probably due to the low dose and frequency of GH administration. Recent short term studies have shown that daily administration of recombinant human GH therapy in varying dosages accelerates growth significantly in short children born SGA (7,(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%